Managing what Matters: An Analysis of Undergraduate Students' Values (2014-2025). The Significance of Managing Based on Values - Mirela POPA (Revista de Management Comparat International)
This longitudinal study explores the evolving personal values of undergraduate business students across 12 academic cohorts (2014–2025), drawing on responses from 4,201 participants. Through non-probability sampling, consistent hierarchies emerged, with Family, Health, Love, Career Success, and Friendship most frequently endorsed, while Travel, Sports, Relaxation, and Partying ranked lowest. Using Maslow’s hierarchy and Schwartz’s value theory, findings reveal a notable post-2020 shift: a decline in self-actualization and esteem values, accompanied by rising emphasis on belonging, security, and basic needs - likely influenced by the COVID-19 pandemic and global instability. Independent samples t-tests confirmed significant decreases in belonging-related values (p = .002) and increases in esteem-related values (p = .039) post-2020. Clustering analyses also identified distinct value groupings: relational/ communal (e.g., empathy, family), individualistic (e.g., career, independence), and expressive-emotional (e.g., creativity, emotional well-being), with integrity and fairness forming a singular moral dimension. These patterns suggest a generational rebalancing from ambition toward connection and security. The findings also highlight a gap between students' consciously stated values and their actual sources of happiness, pleasure, desires and personal satisfaction. The study offers practical implications for educators and employers aiming to align human capital strategies with shifting generational priorities in a post-pandemic world.